The Influence of Perceived Convenience, Security, Cashback and Islamic Financial Behavior on The Decision To Use The Digital Wallet “OVO” On Generation Z Febi Uinsu Students - Lubis, Rizky Aulia; Marliyah, Marliyah; Daulay, Aqwa Naser (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research aims to determine the influence of perceptions of ease of security and cashback on Islamic financial behavior among OVO users, especially Generation Z, Febi Uinsu Regency. Islamic consumption behavior is measured by five basic principles of Islamic consumption behavior. The research method used is associative quantitative. The sample in this study was 75 generation Z respondents in Febi Uinsu Regency who were OVO users using the Hair formula. Data were collected using a questionnaire distributed via the Google Formampling method and using the hair formula. Data processing uses the help of SmartPLS software version 4.0 with the SEM-PLS analysis method. The research results show that the perception of ease of cashback security and sharia financial behavior have an influence on Generation Z’s consumption behavior in using OVO.